Transparent Films Featuring Persistent Luminescence - Fritzen, Douglas Lourenço (2022)
Persistent Luminescence is a visual phenomenon in which a material can absorb light, store it, and then emit light of its own in the dark. Among the applications for materials with persistent Luminescence (PersL), the most common is its use in safety signs, which can be found in buildings almost anywhere in the world. However, other more complex applications are emerging for this class of compounds requiring specific properties, which are not necessarily intrinsic to known persistent materials, making it difficult to advance the use of PersL in the interdisciplinary field. One potentially changing property for PersL materials is transparency. Persistent and transparent materials can greatly expand the application possibilities of this class of compounds. The investigation of the referred doctoral thesis is based on the development of new compounds, which combines transparency with persistent luminescence. For this, the syntheses of the following persistent luminescent materials Sr2MgSi2O7:Eu2+,Dy3+, ZnGa2O4:Mn2+ e Y2O2S:Eu3+,Ti,Mg2+ were optimized and described, and the products obtained were included in a matrix of hydroxypropyl methylcellulose. Finally, the relationship between persistence and transparency properties was evaluated, and three different films were produced one with blue persistence, one with red, and one with green. To better understand the nanoparticles dispersion in the films, a new nanofocused X-ray absorption and emission mapping technique based on Synchrotron radiation was applied.